1997
DOI: 10.1073/pnas.94.10.5162
|View full text |Cite
|
Sign up to set email alerts
|

The origin and evolution of animal appendages

Abstract: Animals have evolved diverse appendages adapted for locomotion, feeding and other functions. The genetics underlying appendage formation are best understood in insects and vertebrates. The expression of the Distal-less (Dll) homeoprotein during arthropod limb outgrowth and of Dll orthologs (Dlx) in fish fin and tetrapod limb buds led us to examine whether expression of this regulatory gene may be a general feature of appendage formation in protostomes and deuterostomes. We find that Dll is expressed along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
273
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(284 citation statements)
references
References 51 publications
6
273
0
5
Order By: Relevance
“…1) expression resembles the antibody staining pattern published by Panganiban et al (1997). Therefore, both methods are likely to reflect the natural ceh-43 expression pattern.…”
Section: Ceh-43::gfp Is Expressed In Hypodermal Cells Neuronal Suppomentioning
confidence: 54%
See 2 more Smart Citations
“…1) expression resembles the antibody staining pattern published by Panganiban et al (1997). Therefore, both methods are likely to reflect the natural ceh-43 expression pattern.…”
Section: Ceh-43::gfp Is Expressed In Hypodermal Cells Neuronal Suppomentioning
confidence: 54%
“…We believe that this expression may not reflect the natural ceh-43::gfp expression, because it is not consistent with the antibody staining from Panganiban et al (1997).…”
Section: Ceh-43::gfp Is Expressed In Hypodermal Cells Neuronal Suppomentioning
confidence: 80%
See 1 more Smart Citation
“…In animal systems where function of Dll genes has been determined, it has been found that Dll function is required for appendage outgrowth in many, but not all, cases. The fact that Dll is expressed at the distal tip of all body wall outgrowths, including the tube feet of starfish (Panganiban et al, 1997), suggests that this gene performed a function required to initiate such outgrowth in the bilateral ancestor of vertebrates and invertebrates (Panganiban, 2000;Zerucha and Ekker, 2000).…”
Section: P/d Axismentioning
confidence: 99%
“…For example, a series of investigations showed that all bilateralia, including humans, possess a common genetic mechanism for patterning the anterior/posterior (A/P) body axis involving the Hox cluster genes (McGinnis and Krumlauf, 1992), the dorsal/ventral (D/V) body axis DeRobertis and Sasai, 1996), and the three derived axes of the appendages (A/P, D/V, and proximo/distal [P/D]) (Irvine and Vogt, 1997;Panganiban et al, 1997;Shubin et al, 1997). Many of the pathways involved in this discussion are covered in more detail in other sections of the book, but here we use them to illustrate the validity of studying model organisms.…”
Section: Reconstructing the Common Ancestor Of Metazoans: Our Distantmentioning
confidence: 99%